9x + 27 = 9(x + 2) + 9
Simplify both sides of equation:
9x + 27 = 9(x + 2) + 9
9x + 27 = (9)(x) + (9)(2) + 9 (Distribute)
9x + 27 = 9x + 18 + 9
9x + 27 = (9x) + ( 18 + 9)
(Combine Like Terms:)
9x + 27 = 9x + 27
9x + 27 = 9x + 27
Subtract 9x from both sides:
9x + 27 - 9x = 9x + 27 - 9x
27 = 27
Subtract 27 from both sides:
27 - 27 = 27 - 27
0 = 0
Equations is always true
Answer: All real numbers are solutions: (Infinitely many solutions:)
Hope that helps!!! ( Answer: Letter Choice (B), Infinitely many solutions.).